Konsep Ekonomi Islam Jalan Tengah (Kapitalis - Sosialis) - Muhammad Tho’in (ITB AAS INDONESIA Surakarta, 2015)
This study aimed to explore how the actual concept of Islamic economics as a middle way that stands between a socialist economic system and the capitalist economic system, as well as whether the greatest challenge of Islamic economics. Type of the research is a qualitative research method, literature.The results obtained by the capitalist system and the socialist economic system have not able to realize prosperity and justice for both individuals as part of the state (socialist economic system) and the public at large or the workers (the capitalist economic system). So inevitably need for a breakthrough by developing the concept of an Islamic economic system msebagai middle way by combining two forms of the previous economic system, the capitalist economic system and the economic system of socialism. This unification effort is made to take the positive side and the dynamic of the two. Meanwhile, the great challenge of Islamic economics is faced with two things, namely poverty and ignorance.